2014
DOI: 10.1371/journal.pone.0092607
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sleep Quality and C-Reactive Protein: Results from National Health and Nutrition Examination Survey, 2005-2008

Abstract: ObjectiveOur objective was to explore the association between poor sleep quality and hs_CRP in an adult U.S. population.MethodsThis study focused on 9,317 participants in the National Health and Nutrition Examination Survey (NHANES) from 2005–2008 who were aged 20–85 years, completed a sleep disorder questionnaire, and had available information on serum hs_CRP. Sleep quality was classified into three categories (good, moderate, poor) based on the responses of participants to the NHANES sleep disorder questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 38 publications
3
28
0
Order By: Relevance
“…Cumulative evidence further shows that inflammation status is related to the patterns of sleep disturbance such as sleep duration and efficiency as well as by gender, age, and comorbid diseases [29]. Hs-CRP has been demonstrated to be a very sensitive measure of systemic inflammation Recently, several large epidemiological and clinical studies have explored the association between poor sleep quality and hs-CRP [15,30]. Liu and colleagues found that poor sleep quality was associated with elevated plasma levels of hs-CRP in females but not in males in a U.S. adult population [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cumulative evidence further shows that inflammation status is related to the patterns of sleep disturbance such as sleep duration and efficiency as well as by gender, age, and comorbid diseases [29]. Hs-CRP has been demonstrated to be a very sensitive measure of systemic inflammation Recently, several large epidemiological and clinical studies have explored the association between poor sleep quality and hs-CRP [15,30]. Liu and colleagues found that poor sleep quality was associated with elevated plasma levels of hs-CRP in females but not in males in a U.S. adult population [15].…”
Section: Discussionmentioning
confidence: 99%
“…Hs-CRP has been demonstrated to be a very sensitive measure of systemic inflammation Recently, several large epidemiological and clinical studies have explored the association between poor sleep quality and hs-CRP [15,30]. Liu and colleagues found that poor sleep quality was associated with elevated plasma levels of hs-CRP in females but not in males in a U.S. adult population [15]. The present study also detected a consistent association between poor global sleep quality and circulating hs-CRP concentrations in menopausal women [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms could be considered as potential mediators for the association between sleep quality and future cardiometabolic risk. These include dysregulation of the hypothalamic-pituitary axis [30], occult obstructive sleep apnea (OSA) [3,31], low-grade inflammation [32], autonomic [33,34] and endothelial dysfunction [35].…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between external and environmental factors (ex: long work days, commute time) with internal factors may share a complex relationship activating physiological pathways [29]. Other commonly proposed mechanisms attempting to explain this relationship include: changes in eating habits [32], changes in hormone regulation altering serum ghrelin and leptin levels causing increased appetite [33], greater fatigue reducing physical activity levels [34], and physiological changes in inflammatory pathways [35,36] and metabolism [37].…”
Section: Journal Of Nutritional Disorders and Therapymentioning
confidence: 99%